A Recently Isolated Lassa Virus From Mali Demonstrates Atypical Clinical Disease Manifestations and Decreased Virulence in Cynomolgus Macaques - Safronetz, David (Oxford University Press, 2013)
The virulence of Soromba-R, a Lassa virus strain recently isolated from southern Mali, was assessed in 2 animal models of Lassa fever: inbred strain 13 guinea pigs and cynomolgus macaques. In both models, the Malian isolate demonstrated tissue tropism and viral titers similar to those of historical Lassa virus isolates from Sierra Leone (Josiah) and Liberia (Z-132); however, the Soromba-R isolate was found to be less pathogenic, as determined by decreased mortality and prolonged time to euthanasia in macaques. Interestingly, in addition to the classic indicators of Lassa fever, Soromba-R infection presented with moderate to severe pulmonary manifestations in the macaque model. Analysis of host responses demonstrated increased immune activation in Soromba-R–infected macaques, particularly in neutrophil-activating or -potentiating proinflammatory cytokines or growth factors, including tumor necrosis factor α, macrophage inflammatory protein 1α, interleukin 1β, and granulocyte colony-stimulating factor, as well as interleukin 5, which may be responsible for the decreased lethality and uncharacteristic clinical presentation. These results suggest that the strain of Lassa virus circulating in Mali might be less pathogenic than strains circulating in the historical region of endemicity and may result in an atypical presentation for Lassa fever, which could complicate clinical diagnosis.